2019
DOI: 10.1111/hepr.13396
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3‐like 1 deficiency ameliorates liver fibrosis by promoting hepatic macrophage apoptosis

Abstract: Aim Chitinase 3‐like 1 (CHI3L1), an 18‐glycosyl hydrolase‐related molecule, is a member of the enzymatically inactive chitinase‐like protein family. Serum levels of CHI3L1 are strongly correlated with hepatic fibrosis progression during many liver diseases. Therefore, this protein could be involved in the development of hepatic fibrosis pathology; however, its role has not been elucidated. We aimed to elucidate its role in the pathophysiology of liver fibrosis. Methods Chitinase 3‐like 1‐deficient (Chi3l1−/−) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…CHI3L1 is highly expressed in liver tissues and is induced in both acute and chronic liver injury in animal models 34 . Studies using knockout mice showed that deletion of CHI3L1 protects against ethanol-induced liver injury 35 and liver fibrosis 36 . However, other groups reported that CHI3L1 protected livers from APAP-induced liver injury by inhibiting the secretion of inflammatory factors and macrophage infiltration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…CHI3L1 is highly expressed in liver tissues and is induced in both acute and chronic liver injury in animal models 34 . Studies using knockout mice showed that deletion of CHI3L1 protects against ethanol-induced liver injury 35 and liver fibrosis 36 . However, other groups reported that CHI3L1 protected livers from APAP-induced liver injury by inhibiting the secretion of inflammatory factors and macrophage infiltration 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are a few of studies on the association of CHI3L1 with liver diseases. For example, Higashiyama et al reported that CHI3L1 promotes liver fibrosis by inhibiting apoptosis in hepatic macrophages. In hepatitis C‐infected population, Kamal et al discovered that CHI3L1 can accurately determine the speed of fibrosis progression, identifying whether the patient is in the stage of rapid fibrosis or stable disease.…”
Section: Discussionmentioning
confidence: 99%
“…A chemical candidate was identified as a CHI3L1 inhibitor to attenuate NF-κB activation and NF-κB-related neuroinflammatory gene expression, 65 and the binding sites were further analyzed by a docking model. 262 It was found that the antibody against CHI3L1 (325-339) peptide reduced the adhesion of chitin-binding protein-overexpressing E. coli to CECs, 186 thereby revealing the importance of the region (325-339) in the CHI3L1 structure. Once the functional domains or structures are fully identified, the chemicals or antibodies will be able to be designed or produced to target them precisely.…”
Section: Closing Thoughtsmentioning
confidence: 99%
“…A recent paper shows that CHI3L1 deficiency ameliorates liver fibrosis by promoting hepatic macrophage apoptosis. 262 However, the exact effect or the involved receptors still remain to be determined. The success of CHI3L1-targeted therapies will depend on whether we can differentiate CHI3L1 functions and its receptors in various biological and pathological responses.…”
Section: Closing Thoughtsmentioning
confidence: 99%